ORIGIN OF RETROGRADE FLUID IN ULTRAHIGH-PRESSURE METAMORPHIC ROCKS: CONSTRAINTS FROM MINERAL HYDROGEN ISOTOPE AND WATER CONTENT CHANGES IN ECLOGITE-GNEISS TRANSITIONS IN THE SULU OROGEN - Chen R.-X.; Zheng Y.-F.; Gong B.; Zhao Z.-F.; Gao T.-S.; Chen B.; Wu Y.-B. (My University, 2007)
By taking advantage of having depth profiles between contrasting lithologies from core samples of the Chinese Continental Scientific Drilling (CCSD) project, a combined study was carried out to examine changes in mineral H isotope, total water and hydroxyl contents in garnet and omphacite across the contacts between ultrahigh-pressure (UHP) eclogite and gneiss in the Sulu orogen, east-central China. The samples of interest were from two continuous core segments from the CCSD main hole at depths of 734.21-737.16 and 929.67-932.86 m, respectively. The results show δD values of -116‰ to - 64‰ for garnet and -104‰ to -82‰ for omphacite, consistent with incorporation of meteoric water into protoliths of UHP metamorphic rocks by high-T alteration. Both equilibrium and disequilibrium H isotope fractionations were observed between garnet and omphacite, suggesting fluid-assisted H isotope exchange at local scales during amphibolite-facies retrogression. While bulk water analysis gave total H2O concentrations of 522-1584 ppm for garnet and 1170-20745 ppm for omphacite, structural hydroxyl analysis yielded H2O contents of 80-413 ppm for garnet and 228-412 ppm for omphacite. It appears that significant amounts of molecular H2O are present in the minerals, pointing to enhanced capacity of water storage in the UHP eclogite minerals. Hydrogen isotope variations in the transition between eclogite and gneiss show correlations with variations in their water contents. Petrographically, the degree of retrograde metamorphism generally increases with decreasing distance from the eclogite-gneiss boundary. Thus, retrograde metamorphism results in mineral reactions and H isotope variation. Because hydroxyl solubility in nominally anhydrous minerals decreases with dropping pressure, significant amounts of water are expected to be released from the minerals during decompression exhumation. Decompression exsolution of structural hydroxyl from 1 m3 volume of eclogite composed of only garnet and omphacite results in release of a quantitative estimate of 3.07-3.44 kg water that can form 140-156 kg amphibole during exhumation. Therefore, it is concluded that fluid for retrogression of the eclogites away from the eclogite-gneiss boundary was derived from the decompression exsolution of structural hydroxyl and molecular H2O in nominally anhydrous minerals. For the eclogites adjacent to gneiss, in contrast, the retrograde metamorphism was principally caused by aqueous fluid from the gneiss which is relatively rich in water. Consequently, both the origin and availability of metamorphic fluid during exhumation of deeply subducted continental crust are deciphered by this combined study focusing on the transitions and the retrograde processes between the felsic and mafic UHP rocks. © 2007 Elsevier Ltd. All rights reserved.